THE FACTORS OF MALAYSIA’S CONSUMER ENGAGEMENT TOWARDS BRAND AWARENESS ON TIKTOK - Nur Hafifa Iswati; Nur Qurratul’ Aini Ismail; Hassad Hassan; Nur Najmilia Zulkifli (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
In the digital era, social media platforms such as TikTok have transformed brand-consumer interactions, emphasizing the importance of understanding consumer engagement and brand awareness for effective marketing. This study examines the factors influencing Malaysian consumer engagement with brand awareness on TikTok, with a particular focus on AI-driven content marketing, influencer impact, and psychological factors. By exploring these elements, the research aims to determine their influence on brand perception and user engagement, guided by specific research questions. As TikTok continues to expand in Malaysia, brands increasingly leverage the platform to reach their target audiences effectively. To enhance the research methodology, a preliminary study was conducted to refine and validate the approach before full-scale implementation, minimizing potential risks and improving overall reliability. The preliminary study involved 30 respondents and findings from the preliminary study ensured that the questionnaire was well-structured and suitable for the main study, reinforcing the study’s credibility in analyzing consumer engagement dynamics on TikTok. This research provides valuable insights into the role of AI content marketing, influencers, and psychological factors in shaping brand awareness and consumer behavior, offering practical implications for brands seeking to optimize their marketing strategies on TikTok.